Choir - Ghosh, Ayan (2023)
St. Thomas church has had a choir ever since the church was founded in 1718. When the church was elevated to the status of cathedral, following the creation of the Diocese of Mumbai in 1837, a choir school was founded for the purpose of training singing boys for divine services. Till the late 1970s, most choristers came from Cathedral & John Connon School.